Field Test of Enhanced Remedial Amendment Delivery Using a Shear‐Thinning Fluid. Issue 3 (2nd March 2015) - Truex, Michael J.; Vermeul, Vince R.; Adamson, David T.; Oostrom, Mart; Zhong, Lirong; Mackley, Rob D.; Fritz, Brad G.; Horner, Jake A.; Johnson, Tim C.; Thomle, Jonathan N.; Newcomer, Darrell R.; Johnson, Chris D.; et al.
Abstract Heterogeneity of hydraulic properties in aquifers may lead to contaminants residing in lower‐permeability zones where it is difficult to deliver remediation amendments using conventional injection processes. The focus of this study is to examine use of a shear‐thinning fluid (STF) to improve the uniformity of remedial amendment distribution within a heterogeneous aquifer. Previous studies have demonstrated the significant potential of STFs for improving remedial amendment delivery in heterogeneous aquifers, but quantitative evaluation of these improvements from field applications is lacking. A field‐scale test was conducted that compares data from successive injection of a tracer in water followed by injection of a tracer in an STF to evaluate the impact of the STF on tracer distribution uniformity in the presence of permeability contrasts within the targeted injection zone. Data from tracer breakthrough at multiple depth‐discrete monitoring intervals and electrical resistivity tomography (ERT) showed that inclusion of STF in the injection solution improved the distribution of the injected fluid within the targeted treatment zone. One improvement was a reduction in the movement of injected fluids through high‐permeability pathways, as evidenced by slower breakthrough of tracer at monitoring locations where breakthrough in baseline tracer‐only injection data was faster. In addition, STF‐amended injection solutions arrived faster and to a greater extent in monitoring locations within low‐permeability zones. ERT data showed that the STF injection covered a higher percentage of a two‐dimensional cross section within the injection interval between the injection well and a monitoring well about 3 m away.